Development and Application of Blast Casting Technique in Large-Scale Surface Mines: A Case Study of Heidaigou Surface Coal Mine in China - Li Ma; Kemin Li; Xiaohua Ding; Hongge Peng; Shuangshuang Xiao (Shock and Vibration)
Blast casting is a high-efficiency technique applied in surface mines for overburden removal and results in stripping cost savings. According to ballistic theory and center-of-mass frame basic movement principles, key factors influencing blast casting effect were analyzed, which include bench height and mining panel width, inclined angle of blast holes, explosive unit consumption (EUC), delay-time interval, presplitting, and blast hole pattern parameters. An intelligent design software was developed for obtaining better breaking and casting effect, and the error rates predicted with actual result can be controlled with 10%. Blast casting technique was successfully applied in Heidaigou Surface Coal Mine (HSCM) with more than 34% of material casted into the inner dump. A ramp ditch was set within the middle inner dump for coal transportation. The procedure of stripping and excavating was implemented separately and alternately in the two sections around the middle ramp ditch. An unconstrained-nonlinear model was deduced for optimizing the shift distance of the middle ramp. The calculation results show that optimum shift distance of HSCM is 480 m, and the middle ditch should be shifted after 6 blast casting mining panels being stripped.